2001
DOI: 10.1542/peds.108.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Experience With the Ketogenic Diet in Infants

Abstract: The ketogenic diet should be considered safe and effective treatment for infants with intractable seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
186
1
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(219 citation statements)
references
References 17 publications
14
186
1
15
Order By: Relevance
“…11,12 In addition, the ketogenic diet has been used for a long time for the treatment of refractory epilepsy. 4,13,14 The protective effect of KB has been mostly attributed to their conversion to AcetylCoA improving mitochondrial metabolism and preserving energy levels. [15][16][17] However, studies suggest that besides providing energy to neurons, KB reduce the production of reactive oxygen species (ROS) contributing to their protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In addition, the ketogenic diet has been used for a long time for the treatment of refractory epilepsy. 4,13,14 The protective effect of KB has been mostly attributed to their conversion to AcetylCoA improving mitochondrial metabolism and preserving energy levels. [15][16][17] However, studies suggest that besides providing energy to neurons, KB reduce the production of reactive oxygen species (ROS) contributing to their protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…In myocardial cells, AA is involved in regulating the incorporation of glucose into glycogen and mediating the relative contributions of exogenous glucose and endogenous carbohydrate to myocardial energy metabolism (52). Interestingly, a ketogenic diet has long been known to be beneficial for the treatment of children with intractable seizures by unknown mechanisms (53,54). These tantalizing reports not only suggest that AA may play important roles in various biological processes but also suggest that it may have regulatory functions in addition to its involvement in energy production.…”
mentioning
confidence: 99%
“…The ketogenic diet was stopped during the first month in seven patients: in two (10, 15) because of inefficacy after 10 days and 3 weeks respectively, and in the five others (3,8,9,20,21) because of adverse events (severe vomiting and fatigue). Although they tolerated the ketogenic diet poorly, these five patients were responders at 1 week, including two who became seizure-free, with seizure control maintained at 1 month (3,9).…”
Section: Results (mentioning
confidence: 99%
“…1,2 Many investigators have confirmed the benefits that this treatment can offer to young patients with epilepsy, [3][4][5][6] including infants. 7,8 However, the best indications for using the diet have not been clearly defined since it was shown to be helpful in treating a large range of different seizure types and epilepsy syndromes. Special interest has been given to various conditions associated with epilepsy including myoclonic astatic epilepsy, 5,9 infantile spasms, 7 Dravet syndrome, 10 atypical absences, 11 acquired epileptic aphasia, 12 tuberous sclerosis, 13 and Rett syndrome.…”
mentioning
confidence: 99%